Light scattering in the human eye modelled as random phase perturbations - Arias, Augusto (Biomed Opt Express, 2018)
Light scattering in the eye affects the quality of vision and its effect increases with aging and related pathologies, such as cataracts. Simulating methods were developed in order to reproduce the effects of this phenomenon. We introduce a statistical model of wavefront perturbations at the pupil plane of the eye that replicates the characteristic angular distribution of the light distribution over the retina. Our approach is based on the parameterization of the discrete cosine spectrum of the wavefront perturbation. The model performance was experimentally validated with a dedicated setup using a liquid crystal on silicon device as a spatial phase modulator. This instrument can be used for further visual experiments with controlled induction of light scattering.